2015
DOI: 10.1111/pme.12808
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sociodemographic Characteristics and Clinical Features in Burning Mouth Syndrome

Abstract: The prevalence of BMS is higher in women, and in married, unemployed, and less highly educated patients. Burning is the most frequent symptom while stressful life events are the most frequent trigger reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
4
22
0
3
Order By: Relevance
“…An oral and peri‐oral burning sensation is the most frequently reported symptom, with patients often describing the pain as scalding, tingling, or numbing (Grushka, Epstein, & Gorsky, ). Other subjective oral symptoms, such as dysgeusia, xerostomia, sialorrhea, and intra‐oral roughness or granularity sensation, have been reported (Adamo et al., ). Commonly, there are no obvious provoking factors, although in some cases BMS patients have reported antecedent dental procedures, the initiation of new medical treatment, or stressful life events (Frutos, Rodríguez, Miralles‐Jorda, & Machuca, ).…”
Section: Introductionmentioning
confidence: 98%
“…An oral and peri‐oral burning sensation is the most frequently reported symptom, with patients often describing the pain as scalding, tingling, or numbing (Grushka, Epstein, & Gorsky, ). Other subjective oral symptoms, such as dysgeusia, xerostomia, sialorrhea, and intra‐oral roughness or granularity sensation, have been reported (Adamo et al., ). Commonly, there are no obvious provoking factors, although in some cases BMS patients have reported antecedent dental procedures, the initiation of new medical treatment, or stressful life events (Frutos, Rodríguez, Miralles‐Jorda, & Machuca, ).…”
Section: Introductionmentioning
confidence: 98%
“…The patient usually links the trigger to the symptoms. In a study performed on 75 patients with BMS, the most frequent trigger reported was stressful life events (45%) and an antecedent dental procedure was present in 20% of the cases 30 .…”
Section: Discussionmentioning
confidence: 99%
“…El paciente vincula normalmente el factor desencadenante a los síntomas. En un estudio realizado en 75 pacientes con SBA, los factores desencadenantes más frecuentemente reportados fueron los acontecimientos vitales estresantes (45%), presentándose las intervenciones dentales recientes en el 20% de los casos 30 .…”
Section: Discussionunclassified